Art brut in America : the incursion of Jean Dubuffet - American Folk Art Museum; Conway, Megan; Dubuffet, Jean, 1901-1985; Hathaway, Norman; Roth, Käthe; Rousseau, Valerie, 1982-; Trickel, Cindy (New York : American Folk Art Museum, 2015)
Published on the occasion of the exhibition "Art Brut in America: The Incursion of Jean Dubuffet," presented October 13, 2015-January 10, 2016, at the American Folk Art Museum, New York, and curated by Valérie Rousseau, Curator, Self-Taught Art and Art Brut -- title page.
Foreword / Anne-Imelda Radice -- Art Brut in America : the incursion of Jean Dubuffet / Valérie Rousseau -- Jean Dubuffet and Alfonso Ossorio / Kent Minturn -- Chicago matters : Jean Dubuffet and the Second City / Jill Shaw -- Collection d l'Art Brut : the wager won by Jean Dubuffet / Sarah Lombardi and Valérie Rousseau -- Collection / Sarah Lombardi and Valérie Rousseau -- Exhibition checklist -- Compagnie de l'Art Brut register -- Acknowledgments -- Photo credits.
Exhibition organized in collaboration with Collection d l'Art Brut Lausanne.
Published on the occasion of the exhibition "Art Brut in America: The Incursion of Jean Dubuffet," presented October 13, 2015-January 10, 2016, at the American Folk Art Museum, New York, and curated by Valérie Rousseau, Curator, Self-Taught Art and Art Brut.
Includes bibliographical references.
Keywords: Dubuffet, Jean, -- 1901-1985 -- Exhibitions; Art brut -- United States -- Exhibitions